2010
DOI: 10.1242/jeb.046938
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tentacle amputation and regeneration on the morphology and activity of the olfactory center of the terrestrial slug Limax valentianus

Abstract: SUMMARYThe tentacles of pulmonates regenerate spontaneously following amputation. The regenerated tentacle is equipped with all the elements necessary for normal olfactory functioning, and the slugs can behave as well as they did before the tentacle amputation. However, it is not known what changes occur to the olfactory center procerebrum in the brain at the morphological and physiological levels. Here, we investigated the innervation of tentacular nerves into the procerebrum by examining the size of the term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 28 publications
3
16
0
1
Order By: Relevance
“…5). Such morphological recovery seems to underlie the ability of slugs with only a pair of regenerated ST (Matsuo et al, 2010b) or pairs of regenerated ST and IT (Fig. 3), to accomplish an odor-aversion learning task.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…5). Such morphological recovery seems to underlie the ability of slugs with only a pair of regenerated ST (Matsuo et al, 2010b) or pairs of regenerated ST and IT (Fig. 3), to accomplish an odor-aversion learning task.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, we demonstrated that the amputated tentacles recover their normal olfactory functions within 34 days (Matsuo et al, 2010b). We thus tested whether the olfactory memory can be retained for a long enough time to allow the amputated tentacles to regenerate.…”
Section: Odor-aversion Memory Is Long-lastingmentioning
confidence: 95%
See 2 more Smart Citations
“…However, across the phylum, a number of structures have been shown to regenerate. These include the foot, anterior neural elements, tentacles, and even the entire head of some gastropods (Moffett, 1995(Moffett, , 1996Gorbushin et al, 2001;Matsuo et al, 2010;Tuchina and Meyer-Rochow, 2010;Hoso, 2012), the siphon and parts of the shell and mantle of some bivalves (Ansell et al, 1999;Tomiyama and Ito, 2006;Nuñez et al, 2013), and the arms, tentacles, and suckers of many cephalopods (Feral, 1978;Bush, 2012;Fossati et al, 2013) including those of giant squid (Aldrich and Aldrich, 1968). Greater sampling of regenerative ability is needed within each of these groups, as well as in the mollusc lineages in which there are no data on regeneration, in order to obtain a clearer picture of the distribution of regenerative ability across this phylum.…”
Section: Molluscamentioning
confidence: 99%